ANALISIS PENGARUH PERSEPSI MANFAAT, KEMUDAHAN PENGGUNAAN DAN KREDIBILITAS TERHADAP MINAT PENGGUNAAN BERULANG INTERNET BANKING DENGAN SIKAP PENGGUNAAN SEBAGAI VARIABEL INTERVENING (Studi Empiris: Nasabah Layanan Internet Banking di Indonesia) - Panggih Rizki Dwi Istiarni; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2014)
This study aims to analyze how the perception of consumers about behavioral intention to use of internet banking to support their daily activities, using TAM framework. The samples in this study using purposive sampling method. Questionnaires from 120 customers of Internet banking services in Indonesia are eligible as samples were analyzed using analysis of Structural Equation Modelling ( SEM ) in AMOS 20.0 program .The results showed that: (1) the perception of usefulness directly influence the attitude of use and indirect effect on the behavioral intention to use, (2) perceived ease of use directly influence the attitude of use and indirect effect on behavioral intention to use, (3) the perception of credibility directly affect stance use and indirect effect on behavioral intention to use, (4 ) the use of attitude and a positive significant effect on behavioral intention to use. The test results are significant and positive provides empirical evidence that people make internet banking is no longer a necessity but a major prestige in carrying out its activities.